Influence of remote processes on a space-time variability of the Amazon River plume - SANTOS, Pedro Tyaquiçã da Silva (2017)
The main objective is to evaluate how teleconnections of chlorophyll-a (Chl) and sea surface salinity (SSS) to oceanic climatic phenomena (e.g. El Niño Southern Oscillation, Atlantic Dipole, etc.). To meet this objective, we addressed: (1) a spatio-temporal variability of Chl and SSS over the Amazon River plume; and (2) the relationship between climatic indexes and spatiotemporal patterns in the variables. The results are presented through three manuscripts submitted to scientific journals. The 10-year MODIS/Aqua dataset was used to determine the seasonal and interannual variability of Chl in the western tropical North Atlantic (WTNA) under the influence of local forcing (Amazon River flow (Q), sea surface temperature (SST), meridional wind stress (y) and zonal current (u)) and remote (canonical (EC) and Modoki (EM) El Niños). There has been a change in ENSO in recent decades to an increasing frequency of EM over EC mode. EM events remotely induce above-normal rainfall over the Amazon basin, which increases Q and nutrient supply in the WTNA. This study suggests that, interannual and annual positive anomalies of Chl concentration in the WTNA depends on rainfall/Q events forced mainly by EM mode. A variability of SST in the Pacific and Atlantic influences strongly precipitation changes in the Amazon River basin, impacting the river flow and consequently SSS in the Amazon plume. An analysis of the Orthogonal Empirical Function (FSO) was performed with 46 years of SST data, rainfall and SSS, in order to establish a relationship between these variables. The results show that the influence of El Niño Modoki on the spatial pattern of rainfall in the Amazon basin is a preponderant factor for positive anomalies of Chl and negative anomalies of SSS over the Amazon River plume. In addition, a characterization of the relationship between a spectral absorption of the colored dissolved organic matter (aCDOM) and the salinity on the Amazon River plume demonstrate the freshwater dispersion and biogeochemical variability in the WTNA. These results support future studies on large-scale climate variability, thermohaline circulation, global hydrological cycle, sediment deposition, biogeochemistry, oceanic fluxes, CO₂ absorption and ecological impacts in the food chain over the WTNA.